2019
DOI: 10.3389/fnagi.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Genetic Factors and Cognitive Reserve on Structural and Functional Resting-State Brain Networks in Aging and Alzheimer’s Disease

Abstract: Magnetic resonance imaging (MRI) offers significant insight into the complex organization of neural networks within the human brain. Using resting-state functional MRI data, topological maps can be created to visualize changes in brain activity, as well as to represent and assess the structural and functional connections between different brain regions. Crucially, Alzheimer’s disease (AD) is associated with progressive loss in this connectivity, which is particularly evident within the default mode network. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 128 publications
1
29
0
Order By: Relevance
“…In order to further understand the relationship between connectivity, Aβ, and selective atrophy, future studies could investigate other variables that could influence resilience and are related to functional connectivity, such as cognitive reserve, longitudinal tau-PET, cardiovascular risk, lifestyle, or genetic factors ( Pietzuch et al, 2019 ). Including years of education did not significantly attenuate the observed effect in our models, however there could be other factors contributing to cognitive reserve in the high-DMN/high-Aβ group.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further understand the relationship between connectivity, Aβ, and selective atrophy, future studies could investigate other variables that could influence resilience and are related to functional connectivity, such as cognitive reserve, longitudinal tau-PET, cardiovascular risk, lifestyle, or genetic factors ( Pietzuch et al, 2019 ). Including years of education did not significantly attenuate the observed effect in our models, however there could be other factors contributing to cognitive reserve in the high-DMN/high-Aβ group.…”
Section: Discussionmentioning
confidence: 99%
“…First, we found that the e4 allele carriers exhibited lower NR and Mod ( p = 0.024, 0.037, respectively) in the study of whole brain DMN using traditional graph-theoretic methods, suggesting the abnormal organization structure in the risk allele group. To our knowledge, there have been few studies ( Luo et al, 2017 ; Pietzuch et al, 2019 ) on graph theory that have reported APOE genotypic differences in functional network properties of whole brain DMN in normal elderly, although a lot of studies have found differences in functional network properties between AD/MCI and NC. Some studies ( Staffaroni et al, 2018 ; Chiesa et al, 2019 ) even found no difference between elderly APOE4+ and APOE4- groups in functional DMN.…”
Section: Discussionmentioning
confidence: 99%
“…At the global whole-brain level, some neurobiologically meaningful graph-theoretic properties have become important indicators for measuring brain functional networks, through which we can understand the altered network architecture in those carrying risk genotype, including a loss of small-world network ( Korthauer et al, 2018 ), a redistribution of hubs ( Wink et al, 2018 ), and a disrupted modular organization ( Li et al, 2019 ). However, there are currently few network measures based on graph theory have been studied in cognitively unimpaired elderly ( Seo et al, 2013 ; Luo et al, 2017 ; Pietzuch et al, 2019 ) and some of their results were reported as inconsistent ( Seo et al, 2013 ; Qiu et al, 2016 ; Luo et al, 2017 ). For instance, Wink et al (2018) found decreased centrality of DMN in APOE4+ comparing to non-carriers, while Wang et al (2017) didn’t find such genotype difference of centrality in normal elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work reported a similar posterior-to-anterior shift pattern in cognitive fatigue (CF) modulation in healthy older adults, suggesting an aging-associated neural reliance on frontal regions to compensate CF-induced cognitive inefficiency (Ren et al, 2019). In addition, the findings in cognitive reserve studies indicate that the brain functional and structural measurements for compensation could be influenced by combination of molecular and genetic factors (Bartres-Faz et al, 2019;Pietzuch et al, 2019).Thus, future studies need to explore the compensatory mechanism in the "posterior-to anterior shift" brain alteration, and reveal the differences between normal aging and psychiatric symptoms. More interestingly, the anterior and posterior brain regions are considered to play different roles in perceived consciousness according to two opposite theories: the global workspace theory (GWT) and integrated information theory (IIT) (Mashour, 2018).…”
mentioning
confidence: 89%